A mesoporous (3, 36)-connected txt-type metal–organic framework constructed by using a naphthyl-embedded ligand exhibiting high CO2 storage and selectivity. Issue 4 (3rd March 2017) - Lu, Zhiyong; Zhang, Jianfeng; He, Haiyan; Du, Liting; Hang, Cheng
Abstract : A highly mesoporous (3, 36)-connected txt-type metal–organic framework with a naphthalene-embedded ligand was successfully synthesized with high CO2 storage capacity and selectivity. Abstract : A highly mesoporous (3, 36)-connected txt-type metal–organic framework, termed HHU-1, with a naphthalene-embedded ligand was successfully synthesized. HHU-1 exhibits a BET surface area of 2290 m 2 g −1 and a high pore volume of 1.33 cm 3 g −1 . Due to the conjugation effect induced by the naphthyl of ligands, acylamide groups stretching into pores contribute to a comparably higher CO2 adsorption enthalpy (27.7 kJ mol −1 ), which endows HHU-1 with a high CO2 storage capacity (1071 mg g −1 at 40 bar) as well as high selectivity (CO2  : N2 = 140).